The Impact of Sport-Specific Imagery on Skill Acquisition and Performance - Dr. Nira Hariyatie Hartani; Dr. Xiaokai Yang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The research study aims to determine the impact of sport-specific imagery on skill acquisition and performance. Based on the primary data analysis for collecting the research data, this study used questions related to the independent and dependent variables. The sport-specific imagery is the main independent variable, and skill acquisition is a mediator between them. Performance is the main dependent variable for measuring the result. For this purpose, SPSS software generated informative results related to the variables. The result shows that descriptive statistics, pair correlation, variance ratio analysis, the regression analysis also present the graphical analysis between them. The overall research study found sport-specific imagery's direct and significant impact on skill acquisition and performance. The resulting study also found that skill acquisition plays a vital role in performance.